2012
DOI: 10.1039/c2ee22665k
|View full text |Cite
|
Sign up to set email alerts
|

Overall photocatalytic water splitting with NiOx–SrTiO3 – a revised mechanism

Abstract: NiO x (0 < x < 1) modified SrTiO 3 (STO) is one of the best studied photocatalysts for overall water splitting under UV light. The established mechanism for this and many other NiO x containing catalysts assumes water oxidation to occur at the early transition metal oxide and water reduction at NiO x . Here we show that NiO x -STO is more likely a three component Ni-STO-NiO catalyst, in which STO absorbs the light, Ni reduces protons, and NiO oxidizes water. This interpretation is based on systematic H 2 /O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
193
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(205 citation statements)
references
References 48 publications
10
193
0
1
Order By: Relevance
“…Surface voltage spectroscopy, the photodeposition of Pt nanoparticles, and (photo) electrochemical measurements suggested that the nickel species contributed to both HER and OER. Ni nanoparticles serve as electron traps and lower the proton reduction overpotential, whereas NiO nanoparticles serve as hole traps and lower the water oxidation overpotential [43]. This view corresponds well with the conclusions of recent works on the coloading of cocatalysts for hydrogen evolution and oxygen evolution, which have found that coloading appropriate amounts of oxygen evolution catalysts can improve the overall water-splitting rate [9,31].…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionssupporting
confidence: 88%
See 1 more Smart Citation
“…Surface voltage spectroscopy, the photodeposition of Pt nanoparticles, and (photo) electrochemical measurements suggested that the nickel species contributed to both HER and OER. Ni nanoparticles serve as electron traps and lower the proton reduction overpotential, whereas NiO nanoparticles serve as hole traps and lower the water oxidation overpotential [43]. This view corresponds well with the conclusions of recent works on the coloading of cocatalysts for hydrogen evolution and oxygen evolution, which have found that coloading appropriate amounts of oxygen evolution catalysts can improve the overall water-splitting rate [9,31].…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionssupporting
confidence: 88%
“…It was suggested that the Ni/NiO core/shell produced the higher photocatalytic activity because the Ni metal between NiO and SrTiO 3 facilitated electron transfer between the photocatalyst and cocatalyst. In contrast, it was recently reported that nickel species prepared using similar procedures on SrTiO 3 consisted of a mixture of Ni and NiO nanoparticles [43]. Surface voltage spectroscopy, the photodeposition of Pt nanoparticles, and (photo) electrochemical measurements suggested that the nickel species contributed to both HER and OER.…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionsmentioning
confidence: 94%
“…Nanoclusters of Ni, Co and their alloys with molybdenum were demonstrated to be potential electrocatalysts for HER [116,117]. Interfacing NiMo alloy nanoparticles with Si microarrays resulted in an effective photocathode that produced impressive photocurrents in the region of 15 mA cm 22 at 0 V versus reversible hydrogen electrode (RHE) powered by one Sun illumination [118].…”
Section: Hybrid Photocatalysts For Proton Reduction and Hydrogen Evolmentioning
confidence: 99%
“…11 In the case of OER, a clear dominant cocatalyst has yet to be established. Several inorganic cocatalysts, such as IrOx, 12 CoOx, 10 Co3O4, 13 NiOx, 9,13 and RuO2, 14 were found to enhance the photocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%